Active ingredients of traditional Chinese medicine for enhancing the effect of tumor immunotherapy - Yang, Chao; Li, Dan; Ko, Chung-Nga; Wang, Kai; Wang, Haiyong (Frontiers in Immunology, 2023)
Immunotherapy is a type of treatment that uses our own immune system to fight cancer. Studies have shown that traditional Chinese medicine (TCM) has antitumor activity and can enhance host immunity. This article briefly describes the immunomodulatory and escape mechanisms in tumors, as well as highlights and summarizes the antitumor immunomodulatory activities of some representative active ingredients of TCM. Finally, this article puts forward some opinions on the future research and clinical application of TCM, aiming to promote the clinical applications of TCM in tumor immunotherapy and to provide new ideas for the research of tumor immunotherapy using TCM.